Application of the Project Citizen Learning Model in Pancasila Education in Improving the Critical Thinking Skills of SMAN 1 Sawan Students - Pratiwi, Putu Meiyanti Setya; Sukadi; Budiarta, I Wayan (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2025)
Abstract This study aims to examine more deeply the implementation of the Project Citizen learning model in Pancasila education in improving the critical thinking skills of SMA Negeri 1 Sawan students. This study uses a qualitative approach with a descriptive method. The data collection technique uses participatory observation and documentation studies. The results of the study show that a socio-philosophical study of Project Citizen learning in the context of Pancasila Education highlights how this model supports the formation of active, critical, and responsible citizens. At SMA Negeri 1 Sawan the project citizen learning model in improving critical thinking skills is applied in several stages, preliminary stages, core and conclusion. The project citizen learning model implemented at SMA Negeri 1 Sawan has been proven to improve the critical thinking skills of students at SMA Negeri 1 Sawan. Critical thinking skills are important for students through a learning approach that emphasizes the analysis of national issues, the formulation of logical opinions, and problem solving based on Pancasila values, students are able to develop a reflective, rational, and responsible way of thinking Keywords: Project Citizen Learning Model, Pancasila Education, Critical Thinking